Criminal [videorecording [(DVD)] - Costner, Kevin; Reynolds, Ryan; Gadot, Gal, 1985-; Jones, Tommy Lee, 1946- (Lionsgate, 2016)
The memories and skills of a CIA agent are implanted into the brain of a dangerous criminal in order to stop an international terrorist.